2021
DOI: 10.7759/cureus.15452
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentations and Outcomes of Coronavirus Disease 2019 in Patients With Solid Tumors

Abstract: BackgroundCoronavirus disease 2019 (COVID-19) is a global health crisis. The literature suggests that cancer patients are more prone to be affected by COVID-19 because cancer suppresses the immune system and such patients usually present poor results. The objective of this study is to present all clinical, laboratory, and demographic characteristics of COVID-19 patients with solid tumors. MethodologyThis study was conducted at the Dow University of Health Sciences for a period of six months from April 2020 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Corpus of literature has reported that the intricate relationship between underlying health conditions and COVID-19 infection [25][26][27][28][29]. Also, as individuals with underlying conditions are diagnosed with COVID-19, they are more likely to die or suffer harsh consequences [17]. Unfortunately, the nding reported here had showed that those who are worse off may have unfavourable attitude towards the vaccination.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Corpus of literature has reported that the intricate relationship between underlying health conditions and COVID-19 infection [25][26][27][28][29]. Also, as individuals with underlying conditions are diagnosed with COVID-19, they are more likely to die or suffer harsh consequences [17]. Unfortunately, the nding reported here had showed that those who are worse off may have unfavourable attitude towards the vaccination.…”
Section: Discussionmentioning
confidence: 88%
“…Also, Sinha and Kundu [30] noted that acquisition of COVID-19 by cancer patients could enhance the development and weaken the individual. In relation to patients with solid tumor, Farooque et al [17] reported a higher mortality among them compared to the general population. The psychological impact of COVID-19, in the form of anxiety, fear, stress and distress, on the general population and affected persons have been noted with a call for further attention paid to enhancing the well-being of the populace [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, the risk factors for COVID-19 include older age, male sex, and pre-existing medical conditions [ [16] , [17] , [18] ]. The European Centre for Disease Prevention and Control outlines health conditions reported among adult patients with severe COVID-19 disease: diabetes [ [18] , [19] , [20] ], obesity [ 21 ], hypertension [ 18 , 22 , 24 ], history of heart failure [ 22 ], solid organ tumors [ 23 ], ischemic heart disease [ 17 , 24 , 26 ], chronic respiratory disease [ 18 , 25 ], cancer [ 25 , 27 ], pregnancy [ 28 , 31 ], neurologic conditions [ 22 , 25 , 26 , 29 ], COPD [ 22 , 24 ], smoking [ 22 , 24 , 30 ] and chronic kidney disease [ [24] , [25] , [26] ].…”
Section: Discussionmentioning
confidence: 99%